2020
DOI: 10.1002/mana.201900128
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on solitons for inverse mean curvature flow

Abstract: Homothetic and translating solitons for the inverse mean curvature flow (IMCF) in ℝ +1 are self-similar solutions deformed by only homothety and translation under IMCF, respectively. In this paper, we address some geometric properties of these solitons. To be specific, the incompleteness for the homothetic soliton of velocity with 0 < < 1 and for any translating soliton are proved. In addition, we show that the quantitative area growth for the homothetic solitons for ≥ 1 and the translating solitons. K E Y W O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…For a translating soliton for the inverse mean curvature flow, Drugan, Lee, and Wheeler [5] gave a translating soliton in R 2 which is the cycloid generated by a circle with radius 1 4 and gave a tilted cycloid product as a translating soliton in R 3 . Kim and Pyo [8,9] showed the existence and classification of rotationally symmetric translating solitons in R n+1 and showed that there is no complete translating soliton for inverse mean curvature flow in R n+1 .…”
Section: Introductionmentioning
confidence: 99%
“…For a translating soliton for the inverse mean curvature flow, Drugan, Lee, and Wheeler [5] gave a translating soliton in R 2 which is the cycloid generated by a circle with radius 1 4 and gave a tilted cycloid product as a translating soliton in R 3 . Kim and Pyo [8,9] showed the existence and classification of rotationally symmetric translating solitons in R n+1 and showed that there is no complete translating soliton for inverse mean curvature flow in R n+1 .…”
Section: Introductionmentioning
confidence: 99%